Inferring potential causative microbial factors of intestinal atrophic disease in the sea cucumber Apostichopus japonicus - Yu, Juanwen; Sawabe, Tomoo; Yamano, Ryota; Koike, Shotaro; Sakai, Yuichi; Mino, Sayaka (Frontiers in Marine Science, 2023)
The overexploitation of the wild populations of Apostichopus japonicus has caused a significant 18 decline in their numbers, prompting the establishment of a sea cucumber aquaculture industry 19 that has become a major player in East Asia. Recent research has focused on identifying the 20 various factors that may affect sea cucumber aquaculture, including water quality, diet and the 21 microbiome associated with their hosts. Notably, studies on host-associated microbiomes have 22 emerged as a prominent area of research, particularly in the context of investigating the 23 relationship of the microbiome to diseases that have caused significant economic losses. 24Intestinal atrophic of A. japonicus larvae has been reported at a number of sea cucumber farms in 25Japan, but there have been no factor screenings and currently there is no efficient mitigation. In 26 this study, we applied metagenomic analyses for the first time to an intestinal atrophic case of the 27 sea cucumber A. japonicus larvae, which occurred in an aquaculture facility in Hokkaido, Japan, 28 elucidating potential causative microbial factors comparing the diseased microbiome against 29 healthy pan-microbiome. Through our metagenome comparisons, we have found significant 30 increases in Oceanicoccus, Ruegeria, Nioella, Labrenzia, Tenacibaculum, and Muricauda in the 31 diseased larvae. Among those, Tenacibaculum was estimated to be potentially the most 32 pathogenic bacterium in the development of intestinal atrophic disease due to previous outbreaks 33 of sea urchin diseases in the same facility. Our metagenomic approach demonstrates the further 34 need of microbial screening of such causative agents and identification of the pathogenesis of 35 such diseases, which could contribute to establishing more sustainable aquaculture in the sea 36 cucumber industry.